Immune responses to methanolic extract of black cumin ( Nigella sativa ) in rainbow trout ( Oncorhynchus mykiss ) - Celik Altunoglu, Yasemin; Bilen, Soner; Ulu, Ferhat; Biswas, Gouranga (Elsevier BV, 2017)
The immune stimulating effects of the methanolic extract of black cumin (Nigella sativa) in rainbow trout (Oncorhynchus mykiss) was evaluated. Variable concentrations of black cumin methanolic extract [0 (Control), 0.1 and 0.5 g kg-1 of feed] were individually added to the basal diet and rainbow trout was fed for 30 days to assess the innate immune responses and growth performance. Feed conversion ratio significantly decreased in the group fed with 0.5 g kg-1 black cumin extract. Respiratory burst activity was observed to be the highest in the 0.5 g kg-1 black cumin extract fed group. Lysozyme and myeloperoxidase activities were significantly increased in fish of experimental groups compared to control (P < 0.05). TGF-β gene expression increased in black cumin 0.5 g kg-1 treated group. IL-1β and TGF-β gene expressions decreased in black cumin 0.1 g kg-1 administered group. Expression of IL-12 gene diminished in both the experimental groups. There was no significant difference in survival rates between black cumin extract treated fish groups and control (P > 0.05) after challenged with Aeromonas hydrophila. The results indicate that the methanolic extract of black cumin is a stimulator of some innate humoral immune responses, but it is ineffective for cytokine-related gene trancriptions in rainbow trout.
Keywords: Plant Extracts; Animal Feed; Immunity, Innate; Aeromonas hydrophila; Diet; Fish Diseases; Oncorhynchus mykiss; Dietary Supplements; Animals; Nigella sativa; Gram-Negative Bacterial Infections; 3. Good health; 14. Life underwater